After Our Esteemed Prof. Mr. Adil Artukoğlu - İrfan Çakın (Türk Kütüphaneciliği)
This is a memoir for decedent Prof. Adil Artukoğlu who was retired Associate Professor of Hacettepe University Department of Librarianship.